Spray simulation of hydrogen fuel for spark ignition engine using computational fluid dynamics (CFD) - Abdul Rahman, Mohd Sabri (2010)
This thesis deals with the numerical study about the simulation of hydrogen fuel in spark ignition engine during the event of compression and combustion process using Computational Fluid Dynamics (CFD). The selection of the combustion model is vital in order to fulfil three major criteria which are accuracy and computational cost. Current study utilised the finite rate/ eddy-dissipation model to simulate the hydrogen fuel combustion and single step reaction mechanism of stoichiometric hydrogen-air mixture is simulated. Turbulence is captured using k-ε-realizable model. Yamaha FZ150i engine has been chosen as the baseline engine design. The simulated engine condition is 2000 rpm while the hydrogen injection pressure is set as 6 bar for a 15o CA of injection period. This project simulates the compression and combustion process between 300 CA until 400 CA. The assessment is based on cylinder pressure inside the enginemodel. The predicted maximum pressure due to hydrogen combustion is 62 bar while maximum temperature is 2687 K. 0.00759 of hydrogen mass fraction is burned during 7o CA of hydrogen combustion period. The pressure data for pressure in engine model is validated using previous experimental data. However, there are discrepancies of the result due to improper boundary condition and inherit limitation of model. For further simulation of combustion process, more data from experimental work is needed such as pressure, temperature and injection data to implement in the simulation.